Best management practices for water quality improvement of Bertam River, Malaysia - Eisakhani, M. (Research India Publications, 2015)
In this study the water quality of Bertam river in Cameron Highlands, Malaysia was investigated. Bertam river is an important source of water for the downstream area and has numerous intake points for drinking purposes. Initially, four sampling points were selected along the river; at its origin (SP1), after Brinchang town (SP2), after Tanah Rata town (SP3) and after addition of Ulung and Batu Pipih rivers (SP4). Total suspended solid (TSS), total nitrogen (N) and phosphorus (P), chemical oxygen demand (COD) and E.coli were identified at each sampling point. Samples were collected in two events; average water flow (AFW) and high water flow (HWF). Results indicate that the river is polluted in all sampling points except SP1. Addition of two tributaries to Bertam river resulted in reduction of pollution in SP4. However, huge concentration of TSS was detected at SP2, 4000 ± 10 mg/L and SP3, 1800 ± 11. Also, high concentrations of total nitrogen (17.2 ± 1.3 and 5.8 ± 0.8 mg/L), phosphorous (14.0 ± 1.1 and 2.6 ± 0.2 mg/L) and COD (50.1 ± 0.9 and 38.9 ± 1.1 mg/L) were identified during HWF at SP2 and SP3, respectively. The finding indicates that nonpoint sources mainly agricultural activities and construction sites are the main pollution contributors in Bertam river. Based on water quality findings and origins of pollution, the best management practices (BMPs) in form of non-structural management are suggested to be implemented for pollution prevention and water quality improvement of Bertam river. © Research India Publications.